Prophylactically Given Tamsulosin in Preventing Postop Urinary Retention in Surgery Under Spinal Anaesthesia - Nishchal Gautam, Shamas Ul Islam, Sadhana Paudel, Fawad Nasrullah (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine effect of tamsulosin in the prevention of post operative urinary retention in patients undergoing spinal anesthesia Study design: Randomized control trial Place and duration of study: Urology Department, Mayo Hospital, KEMU, Lahore February 2020- February 2021 Methodology: Only 106 patients (53 individuals in each group) were included in the study with non probability purposive sampling. The patients undergoing surgery under spinal anaesthesia were either given tamsulosin in one group and not given tamsulosin in other group. Postoperatively patients were monitored for urinary retention. SPSS-26 was used for analyzing the data. Result: Incidence of postoperative urinary retention was significantly higher in placebo group as compared to Tamsulosin group. i.e. (overall result of 26.42 vs 3.77%, p-value=0.001 and 26% vs 2.5% in hernia group and 33.3 vs 7.7 % in hydrocele group) Conclusion: Prophylactically given tamsulosin helps in preventing postoperative urinary retention in patients undergoing surgery under spinal anaesthesia. Keywords: Postoperative urinary retention, Tamsulosin, Spinal Anaesthesia